Analysis of the effect of project-based learning on mathematical creativity skills in cube and block materials - Christiani Mariana Simanullang; Golda Novatrasio Sauduran; Dame Ifa Sihombing (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to investigate the influence of Project-Based Learning (PjBL) on students’ mathematical creativity skills in the topic of cubes and rectangular prisms VII of SMP Swasta TD Pardede Foundation in the academic year 2025/2026. This study is expected to provide a clear description of the extent to which the project-based learning model can enhance students’ creativity in solving mathematical problems, particularly those related to cube and rectangular prism topicsThe type of research used is a quantitative method with a descriptive quantitative approach, which aims to analyze the effect of project-based learning on mathematical creativity skills. The research population consists of eighth-grade students, with a research sample of 60 students selected using purposive sampling.The instruments used were essay-type test items and an observation sheet. The results of simple regression analysis revealed the regression equation Ŷ = 40.126 + 0.508X, with tcount = 2.076 > ttable = 2.002, indicating a positive and significant relationship between the independent variable (Project-Based Learning) and the dependent variable (mathematical creativity skills). Furthermore, the significance test of regression showed that Fcount = 4.309 > Ftable = 4.01 at a 0.05 significance level, suggesting that Project-Based Learning can be used to predict students’ mathematical creativity skills. The coefficient of determination (R²) was 0.539, which means that 53.9% of the variation in mathematical creativity skills is explained by Project-Based Learning, while the remaining 46.1% is influenced by other factors. In conclusion, Project-Based Learning has a considerable and significant effect on enhancing students’ mathematical creativity skills in learning the topic of cubes and rectangular prisms..